Persepsi Industri Chalodo Sibali Resoe Terhadap Penerapan Tarif Pajak Pada UU No. 7 Tahun 2021 - Adhe Widhiakusuma WL; Sofyan Syamsuddin; Sahrir Sahrir (Politeknik Ganesha Medan, 2023)
This study aims to determine the perceptions of the Chalodo Sibali Resoe Industry regarding the imposition of the new tax rate under the HPP Law, that is, if an individual MSME taxpayer has a gross turnover of less than Rp500,000,000.00 per year, the taxpayer is not subject to the MSME final PPh rate. The method used in this study uses qualitative methods, where the respondents of this study are accountants from the Chalodo Sibali Resoe Industry. After conducting research, the results obtained were that the Tax Service Office (KPP) had not conducted a thorough outreach and only discussed the applicable rates. Regarding the imposition of tariffs, it has a positive impact on the finances of the Chalodo Sibali Resoe Industry.